Characterisation of phenylethylamine analogues as calcium channel modulators focusing on transient receptor potential canonical (TRPC) channels - Mak, Yin Ying (2022)
Despite using three or more antihypertensive medications, patients with uncontrolled high blood pressure are diagnosed as having resistant hypertension. Persistent high blood pressure can lead to complications such as stroke, heart disease and kidney problems. Currently, this group of patients are not only taking more antihypertensive medicines but also at higher doses. Inevitably, this leads to a higher risk of adverse events. New molecules targeting different sites of action are the focus of new drug development for this condition. In previous work carried out in our research group, a novel phenylethylamine alkaloid, schwarzinicine A, was isolated from a locally grown fig tree, Ficus schwarzii. It has been shown to relax the rat aorta, porcine coronary and pulmonary arteries. One of its relaxation mechanisms was the inhibition of transient receptor potential canonical (TRPC) channels, particularly TRPC3, 4, 5, 6 channels. Theoretically, schwarzinicine A may possess a lower oral bioavailability as it violated Lipinski’s and Veber’s rules by having a molecular weight (MW) more than 500 Dalton (Da) and 15 rotatable bonds. Furthermore, the yield of schwarzinicine A from natural sources is very low. Hence, N-phenethyl-1,2,3,4-tetrahydronaphthalen-2-amine (FK244) and 1-(furan-2-yl)-N-phenethylpentan-3-amine (PM20), were synthesised based on the pharmacophore of schwarzinicine A. FK244 and PM20 obeyed all criteria outlined in Lipinski’s and Veber’s rules. This thesis investigated the vasorelaxation profile of FK244 and PM20 in rat isolated aorta and focused on characterising their roles in modulating calcium ion (Ca2+) dynamics. To elucidate the underlying pharmacology of these two compounds, isometric tension recordings were performed on Sprague-Dawley (SD) rat isolated aorta using the organ bath technique. FK244 and PM20 displayed a higher drug selectivity in vascular smooth muscle (VSM) tissues. The findings from organ bath experiments have excluded the roles of FK244 and PM20 in regulating NO, cyclic nucleotides, adrenoceptors, and potassium ion (K+) channels as their vasorelaxant mechanisms. The plausible vasorelaxation effects of FK244 and PM20 via an endothelium-dependent route have also been ruled out. FK244 and PM20 significantly suppressed the aortic contractile response to calcium chloride (CaCl2) in a concentration-dependent manner. They also managed to reduce the vascular tone raised by phenylephrine, potassium chloride (KCl) and U46619. Pre-treatment with FK244 and PM20 attenuated phenylephrine-, KCl-, and serotonin-induced vasoconstriction but had no impact on U46619-induced vasoconstriction. However, in a Ca2+-free environment, they did not affect phenylephrine-, KCl- and U46619-induced contraction. These findings suggested that FK244 and PM20 mainly inhibit plasma membrane Ca2+ channels such as L-type voltage-gated Ca2+ channels (VGCCs) and TRPC channels. They do not influence the internal store Ca2+ release involved in smooth muscle contraction. Incubation with TRPC-selective inhibitors 2-aminoethoxydiphenyl borate (2-APB), Pyr3, Pyr6 and SKF-96365 reduced the efficacy of FK244 and PM20. However, the vascular effects of FK244 and PM20 were not affected by nifedipine and verapamil. These results point to a suggestion that FK244 and PM20 could be modulating TRPC channels in addition to L-type VGCCs. Exposure of FK244 and PM20 to C. elegans did not induce toxicity at low concentration but slightly reduced the nematodes’ lifespan at high concentration. Assessment in disease models manifesting hypertension and diabetes have confirmed that the vascular effects of FK244 and PM20 were comparable to that in normotensive SD rats and non-diabetic rats. In addition, fluorometric intracellular Ca2+ recordings were carried out to measure the activity of FK244 and PM20 on TRPC3- and TRPC6-overexpressing human embryonic kidney (HEK) 293 cells. Intracellular Ca2+ measurements in HEK 293 cells have confirmed that FK244 and PM20 blocked extracellular Ca2+ influx via TRPC3 and TRPC6 channels. In summary, FK244 and PM20 displayed significant endothelium-independent vasorelaxation by inhibiting extracellular Ca2+ influx via plasmalemmal Ca2+ channels. One of the targeted Ca2+-permeable channels is TRPC channels, particularly TRPC3 and TPRC6 subtypes. It highlighted TRPC channels as the possible new drug targets in hypertension. TRPC-targeting FK244 and PM20 which prevent vascular contraction, may be developed as antihypertensive agents for resistant hypertension.